Adherence to the Dietary Approaches to Stop Hypertension Dietary Pattern and Risk of Abdominal Aortic Aneurysm: Results From the ARIC Study. Issue 21 (6th November 2018) - Haring, Bernhard; Selvin, Elizabeth; He, Xintong; Coresh, Josef; Steffen, Lyn M.; Folsom, Aaron R.; Tang, Weihong; Rebholz, Casey M.
Abstract : Background: The role of a healthy dietary pattern in the prevention of abdominal aortic aneurysms (AAA) is unknown. We aimed to evaluate the relationship between adherence to a Dietary Approaches To Stop Hypertension‐style dietary pattern and the risk of incident AAAs. Methods and Results: Dietary intake was assessed via a 66‐item food frequency questionnaire at baseline (1987–1989) and at visit 3 (1993–1995) in 13 496 participants enrolled in the ARIC (Atherosclerosis Risk in Communities) study without clinical AAA (mean age, 54 years). A dietary scoring index based on food times was constructed to assess self‐reported adherence to a dietary approaches to stop hypertension‐style dietary pattern. Participants were followed for incident clinical AAAs using hospital discharge diagnoses, Medicare inpatient and outpatient diagnoses, or death certificates through December 31, 2011. Cox proportional hazards models with covariate adjustment were used to estimate hazard ratios with 95% confidence intervals. During a median follow‐up of 23 years, there were 517 incident AAA cases. Individuals with a Dietary Approaches To Stop Hypertension‐style diet score in the highest quintile had a 40% lower risk of hospitalization for AAA than those in the lowest quintile (hazard ratioQ5 vs Q1 : 0.60; 95% confidence intervals: 0.44, 0.83; P trend =0.002). In detailed analyses, higher consumption of fruits, vegetables, whole grains, low‐fat dairy, and nuts and legumes was related to a lower risk for AAA. Conclusions: Greater adherence to a Dietary Approaches To Stop Hypertension‐style dietary pattern was associated with lower risk for AAA. Higher consumption of fruits, vegetables, whole grains, low‐fat dairy as well as nuts and legumes may help to decrease the burden of AAAs.